CD36-Mediated Lipid Accumulation and Activation of NLRP3 Inflammasome Lead to Podocyte Injury in Obesity-Related Glomerulopathy - Jing Zhao; Hong-liang Rui; Min Yang; Li-jun Sun; Hong-rui Dong; Hong Cheng (Mediators of Inflammation)
Podocyte injury critically contributes to the pathogenesis of obesity-related glomerulopathy (ORG). Recently, lipid accumulation and inflammatory responses have been found to be involved in podocyte injury. This study is to explore their role and relationship in podocyte injury of ORG. In animal experiments, the ORG mice developed proteinuria, podocyte injury, and hypertriglyceridemia, accompanied with deregulated lipid metabolism, renal ectopic lipid deposition, activation of NOD-like receptor protein 3 (NLRP3) inflammasome, and secretion of IL-1β of the kidney. The expression of adipose differentiation-related protein (ADRP), CD36, sterol regulatory element-binding protein 1 (SREBP-1), and peroxisome proliferator-activated receptor α (PPARα) in renal tissue were increased. In in vitro cell experiments, after cultured podocytes were stimulated with leptin, similar to ORG mice, we found aggravated podocyte injury, formatted lipid droplet, increased expression of ADRP and CD36, activated NLRP3 inflammasome, and released IL-1β. In addition, after blocking CD36 with inhibitor sulfo-N-succinimidyl oleate (SSO) or CD36 siRNA, activation of NLRP3 inflammasome and release of IL-1β are downregulated, and podocyte injury was alleviated. However, after blocking NLRP3 with MCC950, although podocyte injury was alleviated and release of IL-1β was decreased, there was no change in the expression of CD36, ADRP, and intracellular lipid droplets. Taken together, our study suggests that CD36-mediated lipid accumulation and activation of NLRP3 inflammasome may be one of the potential pathogeneses of ORG podocyte injury.